Learn API testing : norms, practices, and guidelines for building effective test automation - Jain, Jagdeep (Apress, 2022)
Explore software web application architecture, API testing, coding practices, and the standards for better API test automation development and management. This book focuses on aspiring software testing engineers currently working in API testing, and those starting their journey in the field of software testing. You'll begin with an introduction to API testing and software web applications involving APIs. The book then moves on to the authentication standards used in the software industry, and the tools, the frameworks, and the libraries used in API testing. As the book progresses, you'll learn about the test pyramid, how to test an API, what makes a good test script, and various coding guidelines. Finally, you get to write your own API test script. Learn API Testing is your pathway to understanding a typical software web application, its requests and responses, and the properties of a good test script. What You'll learn Examine practices, standards, and guidelines for effective test automation Work with different tools like RestAssured, Curl, and Postman Understand API testing paradigm (internal/external APIs, CDCT) Review a case study on the industrial software API testing process Organize a test framework Who This Book Is For API testing aspirants, developers/architects, project managers, and non-technical team members who may want to understand how APIs are being tested.